Effect of seminal plasma and the freezing process on goat bucks sperm quality - Esteve, Inés Carolina (2024)
In goat bucks the seminal plasma (SP) must be removed before freezing for obtaining surviving the process when egg yolk- or skimmed milk (SM)-based extenders are used. It is clear that SP is prejudicial during the freezing-thawing process in this species but the stage at which SP is lethal for the sperm remains unelucidated. For this reason, the objective of this study was to study the effect of seminal plasma on goat buck sperm quality in each of the stages of the semen freezing process (F:after centrifugation and addition of the first diluent; R: after reaching 4°C; G: after addition of the extender containing glycerol; E: after 90 min of equilibration with glycerol at 4°C; T: after freezing-thawing). Twenty-one ejaculates from seven goat bucks from Murciano-Granadina breed were used in the study. Each of the ejaculates was split into two samples: one of them was processed with SP (SP+) and in the other one the SP was removed (SP-) before freezing. Samples were frozen with a SM-glycerol extender (SM2) and sperm quality (motility and sperm plasma membrane integrity (PMI), acrosomal integrity and mitochondrial functionality) was evaluated at each of the points of the freezing protocol (F, R, G, E and T). The results showed significant differences (p<0.05) in all the quality parameters analyzed, varying among the different stages in terms of significance. The analyses determined that the quality of samples processed without SP was superior to samples processed with SP. The most affected stages were the addition of glycerol and thawing. For the glycerol stage, values in samples with SP+ were 50 % total motile and 34 % live with intact acrosome versus 70 % and 56 %, respectively. In the case of the thawing stage it was more evident, values in samples SP+ were 7 % total motile and 4 % live with intact acrosome versus 40 % and 28 %, to samples SP-. In conclusion, the SP deteriorates the spermatozoa through all the steps of the freezing protocol. However, the stage that affected the most the sperm quality was the freezing-thawing